ANALISIS RANCANGAN FAKTORIAL TIGA FAKTOR UNTUK OPTIMALISASI PRODUKSI BIOETANOL DARI MOLASES TEBU - Arif SP.MSi, Abdullah Bin; Diyono, Wahyu; Budiyanti, Agus; Richana, Nur (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Bioethanol is a plant-based fuels potential as alternative materials to substitute fossil fuels which are non-renewable. The aim of this study is to get the optimal dose of Saccharomyces cerevisiae as starer, concentration of nitrogen (urea) and fermentation time for the production of bioethanol effectively and efficiently. This study was conducted at the Laboratory of Postharvest Research and Development Institute, Bogor from May to September 2015. The materials used are molasses of sugar cane. The experimental design used was a factorial design with 3 factors. The first factor was the treatment of fermentation time (1, 2 and 3 days). The second factor was the nitrogen concentration (0, 2 and 4 grams). The thirtd factor was the Saccharomyces cerevisiae concentration (1, 1.5 and 2 grams). Each treatment was repeated twice. Observations were made on the characteristics of the raw materials (total sugar content, ash content and calcium content) and the resulting product (total sugar content, alcohol content and yield). Data were analyzed using analysis of variance and Duncan Multiple Range Test (DMRT). The results showed that the addition of starter Saccharomyces cerevisiae and treatment of urea 2 grams each produced the highest yield alcohol with a fermentation time of 3 days.